PENGARUH SUBSTITUSI TEPUNG BERAS MERAH TERHADAP KUALITAS MI BASAH - Pramita, Resti; Faridah, Anni; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
Mi is a favored food of children, adolescents, adults, and the elderly. Processing is still wet noodles made ​​from wheat flour main, people are still consuming more white rice and variety of wet processing of rice flour noodles red no. The study aimed to analyze the influence of quality and distinction susbtitusi brown rice flour 0 %, 30 %, 40 % and 50 % of the quality of the color, texture, aroma, taste of wet noodles. This type of research design completely randomized experiment with three replications . The object of research is wet noodles with brown rice flour substitution of 0 %, 30 %, 40 % and 50 %. This research was conducted in December 2013 by 30 panelists. The analysis is carried out by organoleptic test by test and hedonic level. Hypothesis test results show there are significant use brown rice flour 0%, 30 %, 40 % and 50 % of the wet noodle quality. Substitution of brown rice flour 50 % substitution showed a better effect on the quality of red -brown color, aromas of red rice is flavorful, and the taste is quite noticeably brown rice. Substitution of 0 % and 30 % give effect to the texture and elasticity of the category decision ketidakmudah chewy and rather easily broken. And hedonic test results indicate that the substitution of 50 % liked the most in terms of taste and aroma. Keywords: effect, substitution, brown rice flour, wet noodles